"It is not by choice that I gave birth at home": the social determinants of home births during COVID-19 in peri-urban and urban Kenya, a qualitative study - May Sudhinaraset; Rebecca Woofter; John Mboya; Sarah Wambui; Ginger Golub; Claire-Helene Mershon (BMC, 2023)
Abstract Background The COVID-19 pandemic significantly impacted the provision of global maternal health services, with an increase in home births. However, there are little data on women's decision-making and experiences leading up to home births during the pandemic. The objective of this study is to examine the economic, social, and health system factors associated with home births in Kenya. Methods Community health volunteers (CHVs) and village leaders helped identify potential participants for an in-depth, one-on-one, qualitative telephone interview in Nairobi and Kiambu County in Kenya. In total, the study interviewed 28 mothers who had home births. Results This study identified a number of economic, social, neighborhood, and health system factors that were associated with birthing at home during the COVID-19 pandemic. Only one woman had planned on birthing at home, while all other participants described various reasons they had to birth at home. Themes related to home births during the pandemic included: (1) unmet preferences related to location of birth; (2) burdens and fear of contracting COVID-19 leading to delayed or missed care; (3) lack of perceived community safety and fear of encounters with law enforcement; and (4) healthcare system changes and uncertainty that led to home births. Conclusion Addressing and recognizing women's social determinants of health is critical to ensuring that preferences on location of birth are met.